Village homes : - Francis, Mark (Island Press, 2003)
The Village Homes neighborhood in Davis, California is one of the few long-standing examples of sustainable community design. Mark Francis has been studying Village Homes for more than two decades and brings together existing research and writing on the community, studies about the children of Village Homes he conducted throughout the 1980s, and interviews with many parties involved with the project including designers, residents, gardeners, and maintenance people. Mark Francis takes a critical look at Village Homes, addressing its failures as well as its successes, and examines the question of why, despite its success, this development has not been replicated.